Positive electrode active material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
Patent Information
- Application Number
- CN202280015810.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-02-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-02-02
AI Technical Summary
锂过渡金属复合氧化物中添加的元素的种类和添加量对电池性能影响很大,例如,有时添加元素的种类或量仅发生微小变化就无法实现目标性能
[0015]根据作为本发明的一方案的正极活性物质,能够改善电池的循环特性,提高耐久性。
Smart Images

Figure GDA0004401578430000111 
Figure GDA0004401578430000112 
Figure GDA0004401578430000113
Abstract
Description
Technical Field
[0001] This invention relates to a positive electrode active material for non-aqueous electrolyte secondary batteries and a non-aqueous electrolyte secondary battery using the same positive electrode active material. Background Technology
[0002] In non-aqueous electrolyte secondary batteries such as lithium-ion batteries, the positive electrode active material has a significant impact on battery performance, including input / output characteristics, capacity, and durability. Positive electrode active materials typically use lithium transition metal composite oxides containing metal elements such as Ni, Co, Mn, and Al. The type and amount of elements added to these lithium transition metal composite oxides greatly affect battery performance; for example, sometimes even a slight change in the type or amount of added elements can prevent the achievement of target performance. Therefore, numerous studies have been conducted on the type and amount of added elements in lithium transition metal composite oxides.
[0003] For example, Patent Document 1 discloses a positive electrode active material comprising single particles of a nickel-based lithium composite metal oxide, wherein the lattice of each single particle contains 2500–6000 ppm of a doped metal (selected from one or more of the group consisting of Al, Ti, Mg, Zr, W, Y, Sr, Co, F, Si, Mg, Na, Cu, Fe, Ca, S, and B). Additionally, Patent Document 2 discloses a material with the composition Li… x Ni 1-y Co y-z M z O 2-a X b (M is Al alone, or contains Al as a necessary element and is one or more elements selected from Group 13 or 14 of the periodic table, Mn, Fe, Ti, Zr, Nd, La, Cu, V, Sm, W, Zn, Y, Mg, Sr, Ca, Ba, Cs, Na, and P, and X is a halogen element) indicates the positive electrode active material.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Publication No. 2020-520539
[0007] Patent Document 2: Japanese Patent No. 4197002 Summary of the Invention
[0008] The problem the invention aims to solve
[0009] However, while lithium-excess lithium-transition metal composite oxides with a Li molar ratio exceeding 1 are highly anticipated as a new generation of high-capacity cathode active materials, they suffer from technical challenges such as the easy dissolution of transition metals. It is known that adding F to lithium-excess composite oxides can suppress transition metal dissolution and improve durability, but further improvements in durability are needed.
[0010] The purpose of this invention is to provide a high-capacity positive electrode active material containing lithium excess lithium transition metal composite oxide, which is also a positive electrode active material that improves battery durability.
[0011] Solution for solving the problem
[0012] As a feature of the positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present invention, it comprises the formula Li x Mn y Ni z Si a M f O 2-α F α (where M is at least one element selected from Na, K, Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ge, Sn, Pb, Sc, Ti, V, Cr, Fe, Co, Cu, Zn, Ru, Rh, Re, Pd, Ir, Ag, Bi, Sb, B, Al, Ga, In, P, Zr, Hf, Nb, Mo, W, x+y+z+a+f≤2+A, 1.0<x≤1.2, 0.4≤y≤0.8, 0≤z≤0.4, 0<a≤0.03, 0≤f≤0.05, 0<α≤0.1, 0≤A≤0.03) This is a lithium transition metal composite oxide.
[0013] As one aspect of the present invention, a non-aqueous electrolyte secondary battery comprises: a positive electrode containing the above-mentioned positive electrode active material, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and a non-aqueous electrolyte.
[0014] The effects of the invention
[0015] According to the positive electrode active material as one aspect of the present invention, the cycle characteristics of the battery can be improved and its durability enhanced. Attached Figure Description
[0016] Figure 1 This is a cross-sectional view of a non-aqueous electrolyte secondary battery as an example of an implementation method. Detailed Implementation
[0017] As described above, adding F to lithium-excess lithium transition metal composite oxides can suppress the dissolution of transition metals and improve battery durability, but further improvements in durability are needed. To address this technical problem, the inventors conducted in-depth research and discovered that adding Si to F-containing composite oxides containing at least Mn as a transition metal can significantly improve battery durability. In particular, the durability is further significantly improved when Si and specific elements M are added, preferably two or more elements M.
[0018] Hereinafter, with reference to the accompanying drawings, an example of an embodiment of the positive electrode active material for a non-aqueous electrolyte secondary battery of the present invention and a non-aqueous electrolyte secondary battery using the positive electrode active material will be described in detail. It should be noted that from the outset, it was envisioned that the various embodiments and modifications described below be selectively combined.
[0019] The following describes a cylindrical battery in which the wound electrode body 14 is housed in a bottomed cylindrical outer casing 16. However, the outer casing is not limited to a cylindrical outer casing. For example, it can be a square outer casing (square battery), a coin-shaped outer casing (coin-shaped battery), or an outer casing made of a laminate containing a metal layer and a resin layer (laminated battery). In addition, the electrode body is not limited to the wound type. It can also be a laminated electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked with separators.
[0020] Figure 1 This is a cross-sectional view of a non-aqueous electrolyte secondary battery 10, as an example of an embodiment. (See attached image.) Figure 1 As shown, the non-aqueous electrolyte secondary battery 10 includes a wound electrode body 14, a non-aqueous electrolyte, and an outer casing 16 for housing the electrode body 14 and the non-aqueous electrolyte. The electrode body 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound into a spiral shape with the separator 13 in between. The outer casing 16 is a bottomed cylindrical metal container with an axially open end, and the opening of the outer casing 16 is sealed by a sealing body 17. Hereinafter, for ease of explanation, the sealing body 17 side of the battery is referred to as the upper side, and the bottom side of the outer casing 16 is referred to as the lower side.
[0021] Non-aqueous electrolytes comprise electrolyte salts dissolved in non-aqueous solvents. Examples of non-aqueous solvents include esters, ethers, nitriles, amides, and mixtures of two or more of these. Non-aqueous solvents may also contain halogen-substituted derivatives in which at least a portion of the hydrogen atoms are replaced by halogen atoms such as fluorine. Examples of non-aqueous solvents include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and mixtures thereof. Examples of electrolyte salts include lithium salts such as LiPF6. It should be noted that non-aqueous electrolytes are not limited to liquid electrolytes and can also be solid electrolytes.
[0022] The positive electrode 11, negative electrode 12, and separator 13 constituting the electrode body 14 are all strip-shaped elongated bodies, which are alternately stacked radially in the electrode body 14 by being wound into a vortex shape. To prevent lithium deposition, the negative electrode 12 is formed to be one size larger than the positive electrode 11. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in both the length and width directions (short side direction). The separator 13 is formed to be at least one size larger than the positive electrode 11, for example, two separators are arranged to clamp the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0023] Insulating plates 18 and 19 are respectively disposed above and below the electrode body 14. Figure 1 In the example, the positive lead 20 extends through the through hole in the insulating plate 18 toward the sealing body 17, and the negative lead 21 extends through the outer side of the insulating plate 19 toward the bottom side of the outer can 16. The positive lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate, i.e., the cover 27, of the sealing body 17, which is electrically connected to the internal terminal plate 23, is the positive terminal. The negative lead 21 is connected to the inner bottom surface of the outer can 16 by welding or the like, and the outer can 16 is the negative terminal.
[0024] A sealing gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness of the battery interior. A groove 22 is formed in the outer can 16, a portion of which bulges inward on its side surface to support the sealing body 17. The groove 22 is preferably formed in a ring shape along the circumference of the outer can 16, supporting the sealing body 17 on its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the groove 22 and the opening end of the outer can 16 that seals the sealing body 17.
[0025] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating component 25, an upper valve body 26, and a cover 27 are stacked sequentially from the electrode body 14 side. Each component constituting the sealing body 17 is, for example, circular or annular, and all components except the insulating component 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, with the insulating component 25 sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heating, the lower valve body 24 deforms and breaks by pushing the upper valve body 26 upwards towards the cover 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. If the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cover 27.
[0026] The positive electrode 11, negative electrode 12, and separator 13 constituting the electrode body 14 will be described in detail below, especially the positive electrode active material constituting the positive electrode 11.
[0027] [positive electrode]
[0028] The positive electrode 11 has a positive electrode core and a positive electrode additive layer disposed on the surface of the positive electrode core. The positive electrode core can be a foil of a metal that is stable within the potential range of the positive electrode 11, such as aluminum or aluminum alloy, or a thin film with the metal disposed on the surface. Preferably, the positive electrode additive layer comprises a positive electrode active material, a conductive agent, and a binder, and is disposed on both sides of the positive electrode core. The positive electrode 11 can be manufactured, for example, by coating a positive electrode additive slurry comprising a positive electrode active material, a conductive agent, and a binder onto the positive electrode core, drying the coating, and then compressing it to form a positive electrode additive layer on both sides of the positive electrode core.
[0029] Examples of conductive agents used in the positive electrode binder layer include carbon black, acetylene black, Ketjen black, and graphite. Examples of binders used in the positive electrode binder layer include fluoropolymers such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. These resins can also be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salts, and polyethylene oxide (PEO).
[0030] The positive electrode active material contains the formula Li x Mn y Ni z Si a M f O 2-α F α (where M is at least one element selected from Na, K, Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ge, Sn, Pb, Sc, Ti, V, Cr, Fe, Co, Cu, Zn, Ru, Rh, Re, Pd, Ir, Ag, Bi, Sb, B, Al, Ga, In, P, Zr, Hf, Nb, Mo, W, x+y+z+a+f≤2+A, 1.0<x≤1.2, 0.4≤y≤0.8, 0≤z≤0.4, 0<a≤0.03, 0≤f≤0.05, 0<α≤0.1, 0≤A≤0.03) This is a lithium transition metal composite oxide. The composite oxide is a Li-excess system material with Li, Mn, Si, and F as essential elements and a Li molar ratio to the transition metal exceeding 1. It is a composite oxide in which a specified amount of fluoride ions are introduced and some O is replaced by F.
[0031] The positive electrode active material is mainly composed of the composite oxide shown in the above composition formula. Here, the main component refers to the component with the highest mass ratio among the constituent components of the composite oxide. In the compound layer of the positive electrode 11, as the positive electrode active material, composite oxides other than those shown in the above composition formula (e.g., non-Li excess composite oxides, composite compounds that do not contain fluoride ions) can be used, but the content of the above composite oxides is preferably 50% by mass or more, and in practice it can also be 100% by mass. It should be noted that the composition of the composite oxide can be determined using an ICP emission spectrometer (Thermo Fisher Scientific iCAP6300).
[0032] The lithium transition metal composite oxide shown in the above composition preferably contains Ni in addition to Li, Mn, and Si. Ni contributes to high capacity. Adding Si to the lithium transition metal composite oxide shown in the above composition, preferably the composite oxide containing Ni, can improve battery durability, but the simultaneous presence of Si and element M can more effectively improve durability. Therefore, the composite oxide preferably contains at least one element M selected from Na, K, Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ge, Sn, Pb, Sc, Ti, V, Cr, Fe, Co, Cu, Zn, Ru, Rh, Re, Pd, Ir, Ag, Bi, Sb, B, Al, Ga, In, P, Zr, Hf, Nb, Mo, and W as an essential element.
[0033] The above composition formula Li x Mn y Ni z Si a M f O 2-α F α In this process, element M is preferably selected from at least two elements chosen from Na, K, Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ge, Sn, Pb, Sc, Ti, V, Cr, Fe, Co, Cu, Zn, Ru, Rh, Re, Pd, Ir, Ag, Bi, Sb, B, Al, Ga, In, P, Zr, Hf, Nb, Mo, and W. Preferably, at least two elements are selected from Al, P, Sb, Sr, Ti, Mg, and Nb. Adding two or more elements M significantly improves durability. It should be noted that when containing two or more elements M, the total molar ratio of element M should be 0.05 or less (0 < f ≤ 0.05).
[0034] In the lithium transition metal composite oxide shown in the above composition, element M preferably contains three or more elements. The improvement in durability becomes more significant by adding Si and three or more elements M to the lithium transition metal composite oxide containing Mn, Ni, and F. The number of elements M contained, for example, at 0.2 mol% or more, can be four or more, but is preferably one to three, more preferably two or three, and particularly preferably three.
[0035] It should be noted that, since Co is particularly rare and expensive, lithium transition metal composite oxides can also be substantially Co-free. Considering production costs, it is preferable to be substantially Co-free. According to the lithium transition metal composite oxides shown in the above composition formula, even if other elements M are used to replace Co, the same or better durability improvement effect can be obtained as when Co is used.
[0036] The above composition formula Li x Mn y Ni z Si a M f O 2-α F α In this composition, the molar ratio (x) of Li is 1.0 < x ≤ 1.2, preferably 1.1 ≤ x ≤ 1.2. The molar ratio (y) of Mn is 0.4 ≤ y ≤ 0.8, preferably 0.45 ≤ y ≤ 0.60. When the molar ratio of Li to Mn is within this range, it is easy to achieve both high durability and high capacity. Ni is an optional component, but it is preferred to contain it, for example, in a smaller amount than Mn. From the viewpoint of balancing high durability and high capacity, the preferred content (molar ratio) of Ni is 0.05 ≤ z ≤ 0.3.
[0037] The above composition formula Li x Mn y Ni z Si a M f O 2-α F αIn this embodiment, the total molar amount (x+y+z+a+f) of Li, Mn, Ni, Si, and element M is 2+A or less, and A is 0.03 or less. Mn, Ni, Si, and element M are present at octahedral sites in the crystal structure of the composite oxide, but sometimes some Si may also enter the tetrahedral sites of the crystal structure. In this case, the total molar amount (x+y+z+a+f) is expected to exceed 2. The composite oxide in this embodiment is, for example, a Li-excess type composite oxide, not a cation-excess type composite oxide. Or it is a Li-excess type composite oxide and a cation-excess type composite oxide. In addition, the molar ratio (α) of F is 0.1 or less (0<α≤0.1), preferably 0.05≤α≤0.085. When the content of F is within this range, high capacity can be ensured while sufficiently suppressing the dissolution of transition metals, which helps to improve durability.
[0038] The above composition formula Li x Mn y Ni z Si a M f O 2-α F α In this process, the molar ratio (a) of Si is 0.03 or less (0 < a ≤ 0.03), preferably 0.002 ≤ a ≤ 0.015, 0.002 ≤ a ≤ 0.010, or 0.002 ≤ a ≤ 0.005. Even a small amount of Si contributes to improved durability, but the improvement becomes more significant when it exceeds 0.2 mol% relative to the total molar percentage of elements other than Li, O, and F. On the other hand, even with excessive Si content, the improvement in durability has its limits, and it can sometimes affect other battery performance aspects such as capacity. Therefore, to efficiently and effectively improve durability, it is preferable to set the upper limit of the Si content to 1.5 mol%, 1 mol%, or 0.5 mol%.
[0039] The above composition formula Li x Mn y Ni z Si a M f O 2-α F αIn this process, the molar ratio (f) of element M is preferably 0.05 or less (0 < f ≤ 0.05), more preferably 0.04 or less (0 < f ≤ 0.04) or 0.03 or less (0 < f ≤ 0.03). When multiple elements M are included, as described above, the total molar ratio of element M is 0.05 or less. In this case, durability can be improved more efficiently. In addition, when multiple elements M are included, the molar ratio of each element M will vary depending on the type of element, but it is preferably 0.015 or less, 0.01 or less, or 0.005 or less. Element M, even in small amounts, contributes to improving durability when added together with Si, but the improvement in durability becomes more significant when it is 0.2 mol% or more relative to the total molar percentage of elements other than Li, O, and F.
[0040] In the lithium transition metal composite oxide shown in the above composition, the molar ratio (Si to element M) is not particularly limited, but the preferred ratio varies depending on the type of element M. For example, the molar ratio of Si to each element M can be substantially the same. When containing two or more elements M, the total number of moles of element M is preferably greater than the number of moles of Si. When Al is included as element M, for example, the number of moles of Al is greater than or equal to the number of moles of Si, making it greater than the number of moles of other elements M. It should be noted that the lithium transition metal composite oxide may also contain elements other than Li, Mn, Ni, Si, element M, O, and F, without impairing the purpose of the present invention.
[0041] Lithium transition metal composite oxides are, for example, secondary particles formed by the aggregation of multiple primary particles. An example of the median particle size (D50) on a volume basis for lithium transition metal composite oxides is 1–20 μm or 2–15 μm. D50 is the particle size representing the 50% volumetric cumulative value in the particle size distribution determined by laser diffraction scattering. The BET specific surface area of lithium transition metal composite oxides is, for example, 1.0–4.0 mm². 2 / g. Within this range, a BET specific surface area easily balances high durability and high capacity. The BET specific surface area is determined according to the BET method (nitrogen adsorption method) as described in JIS R1626.
[0042] The lithium transition metal composite oxides shown in the above formula can be synthesized, for example, by calcining a mixture of Mn- and Ni-containing carbonates, Si-containing compounds, M-containing compounds, lithium carbonate (Li₂CO₃), and lithium fluoride (LiF). An example of calcination conditions is 700–900 °C for 10–30 hours. It should be noted that the Si-containing compounds can be added to the calcined product after mixing and calcining the other components. In this case, Si readily exists locally on the surface of the lithium transition metal composite oxide particles. Examples of Si-containing compounds include silicon oxide. Examples of M-containing compounds include aluminum oxide, strontium oxide, antimony trioxide, niobium oxide, magnesium oxide, titanium oxide, germanium oxide, phosphorus pentoxide, and lithium phosphate. However, the target compound can be synthesized using other starting materials, not limited to these.
[0043] As described above, the positive electrode active material has the composition formula Li x Mn y Ni z Si a M f O 2-α F α The lithium transition metal composite oxide shown is the main component. This composite oxide preferably contains Ni and element M as essential elements. Element M is preferably selected from two or more elements selected from Al, P, Sb, Sr, Ti, Mg, and Nb. Furthermore, an example of the preferred range for the Si content relative to the total moles of elements other than Li, O, and F is 0.2–1 mol%, and an example of the preferred range for the total M content is 0.2–3 mol%.
[0044] [negative electrode]
[0045] The negative electrode 12 has a negative electrode core and a negative electrode binder layer disposed on the surface of the negative electrode core. The negative electrode core can be a foil of a metal that is stable within the potential range of the negative electrode 12, such as copper, or a thin film with the metal disposed on the surface. Preferably, the negative electrode binder layer contains a negative electrode active material and a binder, and is disposed on both sides of the negative electrode core. The negative electrode 12 can be manufactured, for example, by coating the surface of the negative electrode core with a negative electrode binder slurry containing a negative electrode active material, a conductive agent, and a binder, drying the coating, and then compressing it to form a negative electrode binder layer on both sides of the negative electrode core.
[0046] In the negative electrode mixture layer, the negative electrode active material includes, for example, a carbon-based active material capable of reversibly absorbing and releasing lithium ions. Preferred carbon-based active materials include natural graphite such as flake graphite, block graphite, and amorphous graphite, as well as artificial graphite such as blocky graphite (MAG) and graphitized mesophase carbon microspheres (MCMB). Alternatively, the negative electrode active material can be a Si-based active material composed of at least one of Si and Si-containing compounds, or a combination of carbon-based and Si-based active materials can be used.
[0047] As the conductive agent contained in the negative electrode binder layer, similar to the case of the positive electrode 11, carbon materials such as carbon black, acetylene black, Ketjen black, and graphite can be used. Similar to the case of the positive electrode 11, the binder contained in the negative electrode binder layer can also be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., but styrene-butadiene rubber (SBR) is preferred. Furthermore, the negative electrode binder layer preferably further contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Preferably, SBR is used in combination with CMC or its salt and PAA or its salt.
[0048] [Separator]
[0049] The separator 13 can be a porous sheet with ion permeability and insulation. Specific examples of porous sheets include microporous films, woven fabrics, and nonwoven fabrics. The preferred material for the separator 13 is polyolefin such as polyethylene, polypropylene, copolymers of ethylene and α-olefins, or cellulose. The separator 13 can be either a single-layer structure or a multilayer structure. A heat-resistant layer containing inorganic particles or a heat-resistant layer composed of resins with high heat resistance, such as aromatic polyamide resins, polyimides, or polyamide-imides, can also be formed on the surface of the separator 13.
[0050] Example
[0051] The present invention will be further illustrated below by way of examples, but the present invention is not limited to these examples.
[0052] <Example 1>
[0053] Synthesis of Lithium Transition Metal Composite Oxides
[0054] A carbonate containing Mn and Ni in a 2:1 molar ratio was mixed with silicon oxide, lithium carbonate, and lithium fluoride. The mixture was then calcined in air at 800°C for 20 hours to obtain Li. 1.167 Mn 0.550 Ni 0.275 Si 0.008 O 1.958 F 0.042 The lithium transition metal composite oxide shown is shown.
[0055] [The production of the positive electrode]
[0056] The aforementioned lithium transition metal composite oxide was used as the positive electrode active material. The positive electrode active material, acetylene black, and polyvinylidene fluoride were mixed in a solid component mass ratio of 7:2:1, and N-methyl-2-pyrrolidone (NMP) was used as the dispersion medium to prepare a positive electrode slurry. Next, the positive electrode slurry was coated onto a positive electrode core formed from aluminum foil. After drying and compressing the coating, it was cut to the specified electrode size to obtain the positive electrode.
[0057] [Preparation of non-aqueous electrolytes]
[0058] Ethyl carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in a specified volume ratio. LiPF6 is then added to this mixed solvent to obtain a non-aqueous electrolyte.
[0059] [Preparation of the experimental battery]
[0060] The positive electrode and the negative electrode, formed of lithium metal foil, are arranged opposite each other with a separator to form an electrode body, which is then housed in a coin-shaped outer container. After injecting the non-aqueous electrolyte into the outer container, the outer container is sealed to obtain a coin-shaped test battery (non-aqueous electrolyte secondary battery).
[0061] <Examples 2-13, Comparative Examples 3-12>
[0062] In the synthesis of lithium transition metal composite oxides, compounds containing element M were mixed in the manner shown in Table 1, with appropriate changes to the types and mixing ratios of raw materials. Except for this (the contents of Li, Ni, Mn, O, and F were the same as in Example 1), test cells were fabricated in the same manner as in Example 1. It should be noted that oxides were used for the compounds containing Al, Co, P, Sb, Sr, Ti, Mg, and Nb, respectively.
[0063] <Comparative Example 1>
[0064] In the synthesis of lithium transition metal composite oxide, no silicon oxide was added. Otherwise, the test cells were prepared in the same manner as in Example 1.
[0065] <Comparative Example 2>
[0066] In the synthesis of lithium transition metal composite oxide, no silicon oxide or lithium fluoride was added. Otherwise, the test cells were prepared in the same manner as in Example 1.
[0067] For each test battery in the Examples and Comparative Examples, the capacity retention rate was evaluated using the following method, and the evaluation results are shown in Table 1 together with the content of Si and element M in the positive electrode active material.
[0068] [Evaluation of Capacity Maintenance Rate]
[0069] The capacity retention rate is calculated using the following formula based on the discharge energy E1 (initial discharge energy) after one cycle and the discharge energy E22 after 22 cycles of the following cyclic test.
[0070] Capacity maintenance rate = (E22 / E1)
[0071] <Cyclic Test>
[0072] For the test battery, at a temperature of 25°C, (1) it was charged with a constant current of 0.05C until the battery voltage became 4.7V, and then charged with a constant voltage of 4.7V until the current value became 0.025C, (2) then stopped for 20 minutes, (3) then discharged with a constant current of 0.05C until the battery voltage became 2.5V, (4) and finally stopped for 20 minutes. The process of (1) to (4) was regarded as one charge-discharge cycle, and the cycle was repeated for 22 cycles.
[0073] [Table 1]
[0074]
[0075] [Table 2]
[0076]
[0077] [Table 3]
[0078]
[0079] [Table 4]
[0080]
[0081] As shown in Table 1, compared with the test batteries of Comparative Examples 1 and 2, the test batteries of Examples 1 and 2 exhibited higher capacity retention and superior cycle characteristics. When F was added to the lithium transition metal composite oxide containing Mn and Ni, although the capacity retention of the test battery using this oxide improved, the improvement was less significant compared to the effect when using the composite oxide with added Si. Furthermore, even compared to the cases where Co was added to replace Si (Comparative Examples 3 and 4), the test battery of Example 1 exhibited superior cycle characteristics.
[0082] As shown in Tables 2 to 4, by using lithium transition metal composite oxides with 1 to 3 elements M added to Si, the capacity retention of the experimental batteries was greatly improved, and the cycle characteristics were more effectively enhanced. The combinations of 2 and 3 specific elements M showed particularly significant improvement effects.
[0083] It should be noted that the examples show the use of Al, P, Sb, Sr, Ti, Mg, and Nb as element M. However, it is conceivable that improvements in durability can also be achieved by using other elements or substitutes for these elements such as Na, K, Ca, Ba, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ge, Sn, Pb, Sc, V, Cr, Fe, Cu, Zn, Ru, Rh, Re, Pd, Ir, Ag, Bi, B, Ga, In, Zr, Hf, Mo, and W.
[0084] Explanation of reference numerals in the attached figures
[0085] 10 Non-aqueous electrolyte secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer can, 17 Sealing body, 18, 19 Insulating plate, 20 Positive lead, 21 Negative lead, 22 Groove section, 23 Internal terminal plate, 24 Lower valve body, 25 Insulating component, 26 Upper valve body, 27 Cover, 28 Sealing gasket
Claims
1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising the formula Li x Mn y Ni z Si a M f O 2-α F α The lithium transition metal composite oxide shown in the formula is as follows: M is at least two elements selected from Na, K, Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ge, Sn, Pb, Sc, Ti, V, Cr, Fe, Co, Cu, Zn, Ru, Rh, Re, Pd, Ir, Ag, Bi, Sb, B, Al, Ga, In, P, Zr, Hf, Nb, Mo, W, x+y+z+a+f≤2+A, 1.0<x≤1.2, 0.4≤y≤0.8, 0≤z≤0.4, 0<a≤0.03, 0<f≤0.03, 0<α≤0.1, 0≤A≤0.
03.
2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, Composition formula Li x Mn y Ni z Si a M f O 2-α F α In this context, M represents at least two elements selected from Al, P, Sb, Sr, Ti, Nb, and Mg.
3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein, Composition formula Li x Mn y Ni z Si a M f O 2-α F α In this case, the molar ratio of Si, a, is 0.002 ≤ a ≤ 0.
015.
4. A non-aqueous electrolyte secondary battery, comprising: A positive electrode comprising the positive electrode active material according to any one of claims 1 to 3, negative electrode, The separator sandwiched between the positive and negative electrodes, and Non-aqueous electrolyte.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery and method for producing same
JP2020520539A
Precursor, method for manufacturing active material, and lithium ion secondary battery
JP2012038562A